2019
DOI: 10.1002/hbm.24838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine and midazolam on resting state connectivity and comparison with ENIGMA connectivity deficit patterns in schizophrenia

Abstract: Subanesthetic administration of ketamine is a pharmacological model to elicit positive and negative symptoms of psychosis in healthy volunteers. We used resting-state pharmacological functional MRI (rsPhfMRI) to identify cerebral networks affected by ketamine and compared them to the functional connectivity (FC) in schizophrenia.Ketamine can produce sedation and we contrasted its effects with the effects of the anxiolytic drug midazolam. Thirty healthy male volunteers (age = 19-37 years) underwent a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…For the SN, in our previous work, we only identified a slight reduction in functional connectivity strength by using a lower uncorrected threshold [66]. In line with this, in one recent study, midazolam also showed no significant changes in the functional connectivity strength for the SN [78]. As for the DAN and DMN, results of the drug effect are still inconsistent.…”
Section: Functional Connectivity During Midazolam-induced Sedationsupporting
confidence: 73%
See 2 more Smart Citations
“…For the SN, in our previous work, we only identified a slight reduction in functional connectivity strength by using a lower uncorrected threshold [66]. In line with this, in one recent study, midazolam also showed no significant changes in the functional connectivity strength for the SN [78]. As for the DAN and DMN, results of the drug effect are still inconsistent.…”
Section: Functional Connectivity During Midazolam-induced Sedationsupporting
confidence: 73%
“…For example, in our previous work, no significant functional connectivity changes within the DMN were observed during midazolam-induced light sedation [66]. In contrast, significant reductions in resting-state functional connectivity for DMN were reported during propofol or ketamine-induced mild sedation [78,88,89]. Midazolam or propofol-induced decrease in consciousness correlates with decreased functional connectivity within the FPN, whereas ketamine administration leads to no significant reduction in the connectivity strength in the FPN [66,88,89].…”
Section: Similar and Contrasting Neuroimaging Results From Studies Wimentioning
confidence: 73%
See 1 more Smart Citation
“…ENIGMA's future developments will include the coordinated analyses of new data modalities (such as resting state and task-related functional MRI [160][161][162][163] , as well as geostatistical and mobile sensor data), and deeper or more refined analyses of current imaging modalities. Diffusion MRI, in particular, is moving towards multi-shell protocols that can better differentiate cellular and microstructural sources of variance that may explain patterns observed with DTI 17 .…”
Section: Extending Imaging Modalities and Computational Approachesmentioning
confidence: 99%
“…Resting state fMRI (rs-fMRI) offers an approach to understand patterns of synchronized brain activity in the resting state, which can further be decomposed into networks with known functions (e.g., default mode, salience, attention networks) (Biswal, Yetkin, Haughton, & Hyde, 1995;Biswal et al, 2010). Harmonized processing of rs-fMRI in ENIGMA has used one of two pipelines: (1) an echo-planar imaging-based pipeline, based on Analysis of Functional NeuroImages (AFNI) software, that does not require the use of a co-registered anatomical MRI dataset (Adhikari et al, 2019a;Adhikari et al, 2018;Adhikari et al, 2019b); and (2) a pipeline known as fMRIprep+, based on the fMRIprep approach (Esteban et al, 2019), which can also be used for analysis of multi-site task-based functional MRI (Veer, Waller, Lett, Erk, & Walter, 2019).…”
Section: T1-weighted (T1w) Mrimentioning
confidence: 99%